THE ROLE OF GOVERNMENT IN THE SECTOR OF COMMERCIAL SERVICES IN PRICING PROCESS - Simon O. Iskajyan (Статистика и экономика)
The article deals with the role of the government in tariff design process. Due to advances in science and technology the sector of services provides more than 80% of GDP in several countries, thus the stable development of this sector is considered to be one of the most essential purposes. The state has three groups of tools through which it influences market processes: monetary, fiscal and administrative. Each group differently influences the tariff design process, but all of them are considered to be external factors of pricing and they are not always stable the market processes as it’s needed.